Vibration measurement using a pseudo-stereo system, target tracking and vision methods. (1st March 2019) - Durand-Texte, Thomas; Simonetto, Elisabeth; Durand, Stéphane; Melon, Manuel; Moulet, Marie-Hélène
Highlights: A single high speed camera pseudo-stereo system is proposed to measure vibrations. A vision method with target tracking is assessed in this context. Simulations are performed to optimize the measurement setup in terms of accuracy. The protocol is successfully applied to measure the displacement of a plate and of a loudspeaker. Abstract: A single high-speed camera pseudo-stereo system, with a four-mirror adapter, is optimised thanks to simulation, in order to measure vibrations. The measurement errors due to several sources of noise are quantified and the impact of key parameters on the measurement accuracy is analysed. A target tracking method, with removable stickers, is assessed in this context and used in combination with vision methods. The protocol is applied to measure the sub-millimeter displacement of a plate, and allows retrieving the full Frequency Response Function and associated Operational Modal Shapes. The results are compared with those obtained with reference methods using an accelerometer and a laser vibrometer. Finally, this optimised setup is used to study the relevance and potential limitations of the approach applied to an electro-acoustic source: a low-frequency loudspeaker.